Implementasi Antarmuka Komunikasi Berbasis Long Range pada IoT Middleware untuk Mendukung Network Interoperability - Galih Bhaktiar Candra; Eko Sakti Pramukantoro; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The characteristics of IoT are heterogeneity of device and the communication interface. The heterogeneity of communication interface in IoT causes network interoperability problems. Network interoperability is discussing about network and communication interfaces used by objects (things in IoT) to connect with other devices. One of the existing developed IoT middleware is to support network interoperability by providing communication using WiFi, BLE, and 6LoWPAN interface. Implementation of BLE, WiFi and 6LoWPAN is a limited development of Wide Personal Area Network, where the range of transmission media is in the same category. In this case, development of different types of communication interface and long distance is needed to support network interoperability. The chosen communication interface to be added is LoRa. In this research, LoRa was chosen and applied because it is type of Low Power Wide Area Network. LoRa is a wireless technology for IoT which is becoming popular because of the transfer of its data in small amounts at short intervals over long distances of communication. LoRa is implemented in IoT middleware as a new communication interface and replaces the 6LoWPAN communication interface. Based on testing, the results obtained indicate that the LoRa communication interface can reach 500 meters with an average delay 0.502 seconds. LoRa can receive data from different sensor nodes. In addition, LoRa can run and receive packages from WiFi and BLE, so that the use of LoRa can append middleware capabilities to support network interoperability.